A topographical survey of habitats types in the area characterized by seagrass meadow of Posidonia oceanica in the southern part of the Gulf of Trieste (Northern Adriatic) - Orlando Bonaca, Martina (Annales. Series historia naturalis, 2002)
According to the national legislation and by considering international documents on nature conservation, the Mediterranean endemic seagrass Posidonia oceanica was included in the latest edition of the Slovenian Red List of Rare and Endangered Species...
Keywords: Adriatic Sea; environmental protection; flora; Jadransko morje; morje; Posidonia oceanica; pozejdonka; sea; varstvo narave; vegetacija